A Model for Self Sufficiency Economy Development of Khumnuea Village, Huachang Sub-district,Jaturapakpimarn District, Roi-Ed Province - Buasorn,, Sirinart; Singhalert, Rangsan; Watha, Auychai (Chophayom Journal, 2016)
The purposes of the research were to analyze current conditions, problems and needs for self-sufficiency economy development of Khumnuea village, Huachang sub-district, Jaturapakpimarn district, Roi-Ed province, 2) to design a model for Self Sufficiency Economy Development of Khumnuea village, and to implement and evaluate the model. The research methodology was divided into three phases. The data was collected by questionnaires and analyzed by the computer program. MANOVA (Repeated Measures) was employed for hypothesis testing. The study showed the primary data of Khumnuea village. There were 47 families in the village, most of people in the village were farmers. Most popular community products were sausage, fermented beef, entrails sausage, and organic vegetables. The problems of self-sufficiency economy development of Khumnuea village consisted of knowledge and professional skills, government support, professional training, yearly drought, and capital. The needs for self-sufficiency economy development of Khumnuea village included professional training, knowledge of the self-sufficiency economy philosophy through study visit to farms of organic vegetables, raising domestic chicken and ducts, raising pig, planting mushroom, raising cow, cat fish and frogs. The model for self-sufficiency economy development of Khumnuea village consisted of six activities : study visit to the best practice village/community, 2) frog farm projects, 3)catfish farm project, 4) organic vegetables farm, 5) mushroom farm project, duck farm project, and domestic chicken farm project. Finally, the findings indicated that the research participants significantly earned more money than before using the model. Additionally, they saved more money from buying consumer products than before using the model because they grew their own organic vegetables and they raised their own animals